Analysis of 275 Planned and 10 Unplanned Home Births - Schneider, Gerd (1987)
The purpose of this study is to describe the outcome in one family practice of planned home births attended by a physician and an experienced birth assistant in a self-selected, but subsequently screened, population over an 11-year period. All but 26 primigravidas were screened out, as were multiple pregnancies and malpresentations. Study parameters included characteristics of the population and maternal and neonatal outcomes. Of 275 intended home confinements, nine were screened out for medical reasons before labour, five in very early labour, and three for failure to progress. Of the 273 who delivered at home, including 10 unplanned births, two were transferred to hospital for postpartum hemorrhage. One neonate was hospitalized for complications. The results of this study, as well as a review of the relevant literature, illustrate that, for a selected population, home birth is a reasonable alternative to hospital.